Any Animal Whatever? Harmful Battery and Its Elements as Building Blocks of Moral Cognition. - Mikhail, John (Ethics, 2014)
This article argues that the key elements of the prima facie case of harmful battery may form critical building blocks of moral cognition in both humans and nonhuman animals. By contrast, at least some of the rules and representations presupposed by familiar justifications to battery appear to be uniquely human. The article also argues that many famous thought experiments in ethics and many influential experiments in moral psychology rely on harmful battery scenarios without acknowledging this fact or considering its theoretical or empirical implications. The unifying factor in all these studies is goal-directed harmful contact, inflicted without consent or justification.